The Relationship between Narcissism, Religiosity, Spirituality and Moral Identity among Adults - Nida Falak Naz,; Bibi, Humaira; Naz, Summaira (PJE, 2025)
One of the most pervasive issues in today's world is narcissism. With the rise of social media platforms which often promotes self-centered behaviours, both societies and individuals are becoming narcissistic. The present research focused on examining the relationship between narcissism, religiosity, spirituality and moral identity among males and females in Pakistan. The study sample consisted of 300 adults with varying degree of education providing and ensuring a diverse and representative population. Results indicated inverse relationship between narcissism and other study variables which suggests that individuals with the higher levels of spirituality, religiosity and moral identity exhibits lower levels of narcissism. These results imply that before mentioned variables could act as potential buffers against narcissism. It was further found that males have higher narcissistic tendencies while females have greater propensity toward religiosity, spirituality, and moral identity. These gender differences may exist due to cultural-specific norms that inculcates and promotes self-centric tendencies among men. Furthermore, while marital status had no statistically significant impact on narcissism and spirituality, it did have a statistically significant impact on religiosity and moral identity, with married individuals exhibiting having greater levels of both as compared to their counterparts. From these findings it could be concluded that religiosity, spirituality, and moral identity could be employed to counteract the negative effects of narcissism in adults. These findings could be valuable for mental health interventions and policymakers in addressing narcissism. They provide a basis for designing programs aimed at reducing narcissistic behaviors by promoting and fostering religiosity, spirituality, and moral identity to enhance overall social harmony. This research contributes valuable insights into the dynamics between narcissism and positive psychological constructs, highlighting potential avenues for intervention and further study.